(untitled) (Eurasian Scientific Herald, 2022)
The article studies the ways of development of retail trade enterprises, the trends of sustainable development of trade enterprises’ turnover, the directions of implementation of competition in the retail trade sector, the main indicators of retail trade and develops conclusions and recommendations for the development of this sphere.